Autologous hematopoietic stem cell transplantation in classical Hodgkin's lymphoma - Cortez,Afonso José Pereira (2011)
BACKGROUND: Hodgkin's lymphoma has high rates of cure, but in 15% to 20% of general patients and between 35% and 40% of those in advanced stages, the disease will progress or will relapse after initial treatment. For this group, hematopoietic stem cell transplantation is considered one option of salvage therapy. OBJECTIVES: To evaluate a group of 106 patients with Hodgkin's lymphoma, who suffered relapse or who were refractory to treatment, submitted to autologous hematopoietic stem cell transplantation in a single transplant center. METHODS: A retrospective study was performed with data collected from patient charts. The analysis involved 106 classical Hodgkin's lymphoma patients who were consecutively submitted to high-dose chemotherapy followed by autologous transplants in a single institution from April 1993 to December 2006. RESULTS: The overall survival rates of this population at five and ten years were 86% and 70%, respectively. The disease-free survival was approximately 60% at five years. Four patients died of procedure-related causes but relapse of classical Hodgkin's lymphoma after transplant was the most frequent cause of death. Univariate analysis shows that sensitivity to pre-transplant treatment and hemoglobin < 10 g/dL at diagnosis had an impact on patient survival. Unlike other studies, B-type symptoms did not seem to affect overall survival. Lactic dehydrogenase and serum albumin concentrations analyzed at diagnosis did not influence patient survival either. CONCLUSION: Autologous hematopoietic stem cell transplantation is an effective treatment strategy for early and late relapse in classical Hodgkin's lymphoma for cases that were responsive to pre-transplant chemotherapy. Refractory to treatment is a sign of worse prognosis. Additionally, a hemoglobin concentration below 10 g/dL at diagnosis of Hodgkin's lymphoma has a negative impact on the survival of patients after transplant. As far as we know this relationship has not been previously reported.